Increased Serum PAI-1 Levels in Subjects with Metabolic Syndrome and Long-Term Adverse Mental Symptoms: A Population-Based Study. (2nd March 2010) - Huotari, Anne; Lehto, Soili M.; Niskanen, Leo; Herzig, Karl-Heinz; Hintikka, Jukka; Koivumaa-Honkanen, Heli; Tolmunen, Tommi; Honkalampi, Kirsi; Kaikkonen, Noora; Viinamäki, Heimo
Abstract : Depression is an independent risk factor for cardiovascular diseases and is associated with metabolic syndrome (MetS). Levels of plasminogen activator inhibitor-1 (PAI-1), an inhibitor of tissue-type and urokinase-type plasminogen activators, are associated with MetS. To clarify the role of PAI-1 in subjects with long-term adverse mental symptomatology (LMS; including depression) and MetS, we measured circulating PAI-1 levels in controls (n = 111 ), in subjects with MetS and free of mental symptoms (n = 42 ), and in subjects with both MetS and long-term mental symptoms (n = 70 ). PAI-1 increased linearly across the three groups in men. In logistic regression analysis, men with PAI-1 levels above the median had a 3.4-fold increased likelihood of suffering from the comorbidity of long-term adverse mental symptoms and MetS, while no such associations were detected in women. In conclusion, our results suggest that in men high PAI-1 levels are independently associated with long-term mental symptomatology.